PENGARUH PENGALAMAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN CV. BINTANG UTAMA SEMARANG BAGIAN BODY REPAIR - Vicki Anggraeni Purwanto; Agus Hermani (Universitas Diponegoro, 2017)
CV. Bintang Utama Semarang as a company engaged in the service car repair still found some employees lower performance levels as there is still a low quality work, the number of car repair has not yet reached the target, the independence of the employees is still low, and a high level of customer complaints. It is alleged there are work experience due to the employee and employee discipline assessed was still low.This research aims to find out how the influence exerted by work experience and discipline work against employee performance CV. Bintang Utama Semarang. The type of research used is the type of explanation (eksplanatory research). With the number of samples as much as 58 respondents use the sampling approach saturation. Data collection using the questionnaire with likert scale measurements. Methods of data analysis used is test validity and reliability, the correlation coefficient (R), regression test, the coefficient of determination (R2), the significance of the t-test and F-test.The results of this study showed that the variables work discipline and work experience has significant effects, powerful and positive towards the performance of employees. Two variables was tested in stages or together showed results that work experience variables (0.724) and discipline work (0.783) simultaneously have a relationship that is strong against variable employee performance. The magnitude of the contribution that is owned by the variable work discipline is greater than the magnitude 2of donations owned variable work experience, the value of the coefficient of determination (R2) for the variables work experience of 52.5% and 61,4% of work discipline